Pemanfaatan Awig-Awig dan Perarem dalam Pengelolaan Keuangan Desa Adat - Diantari, Ni Made Ambar; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 29 No 3 (2019), 2019)
The development of accounting isidely applied by social organizations in society. Accountability is seen as not only limited to accountability and guidance for the organization, but has other functions of interaction between the ethical, social, and accounting environment. Traditional villages in Bali carry out accounting functions based on awig-awig and perarem as agreed by all customary officers and customary manners. This research was conducted to find out how indigenous villages can carry out their accounting functions based on awig-awig and perarem. This study using the methods of observation, interviews, and documentation. To ensure the data presented are valid, this study uses triangulation techniques. The results indicate that the use of awig-awig and perarem in the management finances is carried out by the Adat Awan village commander based on understanding and knowledge of funding sources, mobilization and allocation of funds, and financial accountability based on Tri Hita Karana. Keywords : Customary Village; Accountability; Awig-Awig; Perarem.